Desarrollo local y derecho a la educación de los niños ngäbe-bouglé panameños en Costa Rica. - Atencio-Morales, Roy (2014)
Economic development of Coto Brus (Costa Rican bordering with Panama) is based largely on the production of coffee. This production is collected mostly by indigenous Ngäbes-Bougle from Panama.  This population, from September to December, migrate from their territory and arrive with their families. Children of all ages face a reality of exclusion from formal education. The Health sector have outlined some solutions and migration processes were formalized some processes, however, as it pertains to education the subject has not been discussed and year to year continues hiding the fundamental right of these children and girls to participate in formal education. In this paper we develop a description of the economic development of the Canton Coto Brus as fundamental and primary reason for Indians of Panama Ngäbes-Bougle migrate to Costa Rica, also will describe the migration process Ngäbes Bougle and practices of daily life their career development, this view because of the activity of the children in those months of harvesting coffee, Costa Rican law also investigate UN and around the right to education of every human being eventually there will be a proposal for the development of a school that meets with differentiated programs Ngäbes Bougle children, assisting the right of every individual to receive a quality education. The Education Center will be funded by Costa Rican organizations dedicated to the care of people at social risk (IMAS, PANI), by the Ministry of Education, and request an agreement between Costa Rica and Panama for the school has the support of both respective countries as logistics resources and culture.